2011
DOI: 10.1007/s10750-011-0685-5
|View full text |Cite
|
Sign up to set email alerts
|

Resource partitioning in endemic species of Baikal gastropods indicated by gut contents, stable isotopes and radular morphology

Abstract: We used multiple analytical methods to demonstrate resource partitioning in five species of coexisting endemic gastropods in the family Baicaliidae and the genus Megalovalvata (Valvatidae) in rocky walls of the underwater canyons in Lake Baikal. We tested whether filter-feeding baicaliids and valvatids consume and assimilate different food using data from gut contents, stable d 13 C and d 15 N isotopes and radular morphology, with subsequent combined analyses. Our results showed that the four baicaliid species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
(43 reference statements)
2
15
0
1
Order By: Relevance
“…Investigations into gastropod stomach contents showed that most diatom cells were broken and empty, but some diatoms remained intact with preserved plastids (Dillon and Davis, 1991;Kawamura et al, 1995Kawamura et al, , 2005). Similar results were described for Baikal gastropods (Sitnikova et al, 2012). The aim of the present study was to determine whether gastropod species employ different mechanisms for breaking frustules for large and small diatom cells.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Investigations into gastropod stomach contents showed that most diatom cells were broken and empty, but some diatoms remained intact with preserved plastids (Dillon and Davis, 1991;Kawamura et al, 1995Kawamura et al, , 2005). Similar results were described for Baikal gastropods (Sitnikova et al, 2012). The aim of the present study was to determine whether gastropod species employ different mechanisms for breaking frustules for large and small diatom cells.…”
Section: Introductionsupporting
confidence: 72%
“…Both of the snails are able to attach and hang continuously from vertical surfaces and overhanging rock using byssus threads ( Figure 1A) (Roepstorf et al, 2003;Sitnikova et al, 2012). Filtering seston, the gastropods passively ingest food particles from the littoral phytoplankton.…”
Section: > Objects Of the Investigationmentioning
confidence: 99%
See 3 more Smart Citations